A New Chromone from the Flower Buds of Magnolia fargesii and its Anti HIV-1 Activity - Du, Gang; Yang, Liying; Shen, Yanqiong; Shu, Lidang; Wen, Meng-Liang; Hu, Qiu-Fen (Asian Journal of Chemistry, 2013)
A new chromone, fargesiichromone A (1) was isolated from the flower buds of Magnolia fargesii. The structure of newly isolated fargesiichromone (1) was elucidated by spectroscopic methods including extensive 1D and 2D NMR techniques. Compound 1 was also evaluated for the anti HIV-1 activity and it showed anti HIV-1 activity with EC50 4.18 μg/mL, CC50 > 200 μg/mL and therapeutic index value above 47.8.